Too Many Graduates? An Application of the Gottschalk-Hansen Model to Young British Graduates between 2001-2010 - Nigel C. O'Leary; Peter J. Sloane (Institute for the Study of Labor (IZA), 2014)
There is an apparent inconsistency in the existing literature on graduate employment in the UK. While analyses of rates of return to graduates or graduate mark-ups show high returns, suggesting that demand has kept up with a rapidly rising supply of graduates, the literature on over-education suggests that many graduates are unable to find employment in graduate jobs and the proportion over-educated has risen over time. Using a simple supply and demand model applied to UK data that defines graduate jobs in terms of the proportion of graduates and/or the graduate earnings mark-up within occupations, we find that there has been a shift in the likelihood of young British university graduates being employed in non-graduate jobs in the recent years of our analysis. This finding is in contrast to existing studies.
Keywords: I2; J0; J3; 330; education; wages; graduates; mismatch